Raving Fans: A Revolutionary Approach to Customer Service - Sheldon Bowles; Kenneth H. Blanchard (London Thorsons, 2011)
A straightforward and snappy guide to successful customer service from the author of the bestselling The One Minute Manager. Raving Fans, in a nutshell, is the advice given to a new Area Manager on his first day - in an extraordinary business book that will help everyone, in every kind of organisation or business, deliver stunning customer service and achieve miraculous bottom-line results. Raving Fans is written in the parable style of The One Minute Manager and uses a brilliantly simple and charming story to teach how to define a vision, learn what a customer really wants, institute effective systems, and make Raving Fan Service a constant feature - not just a passing fad. Business is in the midst of a service crisis that has left millions of disillusioned customers in its wake. Raving Fans includes startling new tips and innovative techniques that can help anyone create a revolution in any workplace - and turn their customers into raving, spending fans.
Keywords: Business; Nonfiction; Leadership; Management; Self Help; Personal Development; Entrepreneurship; (ETB-2006) Guest Services Management